Pengaruh Terapi Musik terhadap Tingkat Nyeri Pemasangan Infus pada Pasien Anak Usia Prasekolah di Ruang Anak Rumah Sakit Kanker Dharmais Jakarta Tahun 2023 - Rita Donna Marlina; Yuni Susilowati; Rangga Saputra (Pusat Riset dan Inovasi Nasional, 2024)
The infusion procedure can cause problems in children due to pain. Based on preliminary studies, it was found that at least 3 out of 5 pediatric patients who underwent an infusion procedure would cry loudly due to pain. This study is to determine the effect of music therapy on infusion pain in preschool-aged children. This study used Post-test Only Control Group Design which consisted of an experimental group of 9 respondents and a control group of 9 respondents. Based on the univariate statistical test, the results show that most of the respondents in the control group were 6 years old, namely as many as 3 people (33.3%), male as many as 5 people (55.6%), felt pain on a scale of 6-7 as many as 5 people (55.6%) and pain scale 8-9 as many as 4 people (44.4%). While in the intervention group, most of the respondents were 5 years old, consisting of 3 people (33.3%), 6 people (66.7%) were male and 6 people felt pain on a scale of 2-3 (66.7%). Based on the Mann Whitney test, a p value of 0.000 was obtained, meaning that music therapy affected the pain level of infusion in preschool-aged children. The results of this study prove that music therapy is an effective distraction technique for infusion pain levels in preschool-aged children. The results of this study are expected to be a reference for nurses in applying music therapy in reducing pain due to infusion.